Diversity and Distribution of Meroplanktonic Larvae in the Pacific Arctic and Connectivity With Adult Benthic Invertebrate Communities - Ershova, E. A.; Descoteaux, R.; Wangensteen, O. S.; Iken, K.; Hopcroft, R. R.; Smoot, C.; Grebmeier, J. M.; Bluhm, B. A. (Frontiers in Marine Science, 2019)
Pelagic larval stages (meroplankton) of benthic invertebrates seasonally make up a significant proportion of planktonic communities, as well as determine the distribution of their benthic adult stages, yet are frequently overlooked by both plankton and benthic studies. Within the Arctic, the role of meroplanktonic larvae may be particularly important in regions of inflow from sub-Arctic regions, where they can serve as vectors of advection of temperate species into the Arctic. In this study, we describe the links between the distribution of larvae and adult benthic communities of bivalves, echinoderms, select decapods and cnidarians on the Pacific-influenced Chukchi Sea shelf during August-September in the time period 2004-2015 using traditional morphological and molecular tools to resolve taxonomic diversity. For most taxa, we observed little regional overlap between the distribution of larvae and adults of the same taxon; however, larvae of some organisms (e.g., the burrowing anemone Cerianthus sp., the sand dollar Echinarachnius parma) were only observed near populations of adult organisms. Larval stages of species not commonly observed in the Chukchi Sea benthos were also observed in the plankton; overall, shelf meroplanktonic communities were numerically dominated by larvae of coastal hard-bottom taxa, rather than local soft-bottom shelf species. Our results suggest that most larvae that we observe on the shelf are advected from other areas rather than produced locally, and most likely will not successfully settle to the benthos. Seasonality and distribution of water masses were the most important parameters shaping meroplankton communities. We discuss the implications of changing oceanographic and climatic conditions on the potential of range extensions by temperate species into the Arctic Ocean.